An experimental investigation into the validity of Leeson's equation for low phase noise oscillator design - Van der Merwe, John (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.